(untitled) (Journal of Decolonising Disciplines, 2021)
As part of the first year Academic Literacy course at the UFS, students are required to study graded readers. The booklets are abridged versions of Western fiction, therefore these narratives reinforce the colonial presence in our curriculum. But South African students need to read local narratives in order to learn about each other – from each other. By taking part in the Initiative for Creative African Narratives (iCAN) students improve our curriculum by writing their own short stories so that they become contributors of material that will be graded and tested to form part of the UFS Academic Literacy curriculum. Thereby, students contribute to larger bodies of knowledge through their lived experiences. This article reflects on the challenges and opportunities within the iCAN process.